CLICK FRAUD: ADVERTISING AND THE TERRITORIALISATION OF PERSONAL BLOGS - Hopkins, Julian (AoIR Selected Papers of Internet Research, 2014)
Drawing upon Deleuze & Guattari’s concept of the assemblage, and Callon’s actor- network theory analysis of economic markets, this paper draws upon ethnographic research to examine a case study of changing practices amongst personal bloggers in Malaysia. Focusing on cost per click advertising, it shows how stabilising reciprocal practices became recast as ‘click fraud’ by a blog advertising network, and ‘community’ is reframed as an income generating collective.